Funding Tertiary Education for National Development in Nigeria: A Historical Perspective - Oke, Tolulope Idowu; Dang, Philomina Luka (NIU Journal of Social Sciences, 2019)
Higher Education is a veritable tool for socio-economic development of any country. This paper looks at the funding of Higher Education from the historical perspective. Some briefs are made about the history of Higher Education right from the pre-colonial to the post-independence era. Though there seems to be more emphasis on university education, other tertiary institutions like Polytechnics or Monotechnics and Colleges of Education are also surveyed. The role of funding cannot be over emphasized in any meaningful endeavour talk more of tertiary education. The history of the funding follows the pattern of their ownership. It covers the sources of funding whether government (Federal or State) or private. From the public point of view Tertiary Education Trust Fund TETFund is considered a major source of capital expenditure. The paper found that from the beginning funding of tertiary education was sufficient in Nigeria however, the story changed after the oil boom. Today we are faced with infrastructural decay as a result of poor funding. To remedy the situation the paper recommends among others the encouragement of private participation; the raising of the education tax collected/or TETFund from 2% to 5% and the revisiting of the practice of Treasury Single Account (TSA) for our tertiary institutions. Keywords: Funding, Tertiary Education, Sustainable, National Development, Historical Perspective